Analisis Bauran Komunikasi Pemasaran (Café Maknyus) Dalam Meningkatkan Branding - Parawita, Feni; Salas, Hagi Julio; Marini, Marini (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
Indonesia's café industry has experienced significant and accelerated growth, as evidenced by the widespread emergence of cafés across multiple regions, particularly within urban centers. This trend illustrates a shift in consumer lifestyle preferences and highlights the growing demand for strategic marketing communication efforts to enhance sales performance and mitigate business failure risks. This research seeks to explore how marketing communication strategies are applied, drawing upon the theoretical framework of the marketing communication mix. A qualitative research design was adopted, utilizing a case study approach with data gathered through in-depth interviews, direct observations, and relevant documentation. The findings reveal that the marketing communication practices employed encompass advertising, personal selling, sales promotion, direct marketing, public relations, and word-of-mouth marketing. The management of Maknyus Cafe & Resto plays a pivotal role in disseminating key information, ensuring that both promotional content and culinary offerings deliver added value to the target consumer base.